Cytotoxic effects of Nigerian Ethnomedicinal Plant Extracts on Three Cancer Cell Lines and their Antioxidant Properties - Thomas Abu; Omonike Ogbole; Edith Ajaiyeoba; Toluwanimi Akinleye; Adedapo Sanusi; Johnson Adeniji (Shiraz University of Medical Sciences, 2023)
Several chemotherapeutic agents have been associated with cancer treatment but with numerous adverse effects. In this study, the cytotoxic and antioxidant effects of methanol extracts of ten selected plants from Nigerian ethnomedicine were assessed as a probable source of natural products for the treatment of cancer. The phenolics and flavonoid contents, and in vitro antioxidant assays (DPPH, nitric oxide, total antioxidant capacity, ferric reducing antioxidant power, metal chelating, lipid peroxidation) on the plant extracts were evaluated. In vitro cytotoxic effects of the extracts on Brine Shrimps, Rhabdomyosarcoma (RD), Breast (MCF-7), and Cervical (HeLa) cancer cell lines were also evaluated. The plant extracts demonstrated a broad spectrum of antioxidant properties. All the extracts exhibited moderate toxicity on brine shrimp. Pacrilima nitida exhibited the highest inhibition on the growth of RD (CC50=17.97 µg/mL) and MCF-7 (CC50=38.79 µg/mL) cell lines while Cocos nucifera exhibited the highest inhibition on the growth of HeLa (CC50=24.16 µg/mL). These plants exhibited a relatively cytotoxic and antioxidant effect and thus could contribute to anticancer drug discovery and many other disease conditions due to their antioxidant properties.